GAME ONLINE DI KALANGAN MAHASISWA UNIVERSITAS HALU OLEO - Rahmawati Rahmawati (KABANTI : Jurnal Kerabat Antropologi, 2022)
The method of data collection in the study used ethnographic methods that emphasize involved observation, in-depth interviews, interpreting and analyzing various observations, the data were analyzed from the beginning of the research in a qualitative descriptive manner. The research shows that (1) The students in Lalalara Village play online games almost every day. They play from morning until late at night. The place where students play online games is in boarding houses, warkop to campus. The types of online games that are often played are PUB-G Mobile, Call of duty and also Free Fire. (2) The factors that cause Lalolara students who are used as informants in student research who play online games are caused by interesting game features, long enough game play duration, fun playmates and also competencies held by online games. (3) Implications of Lalolara students who play online games. Students who play online games almost forget their surroundings and they even begin to hesitate to interact with their surroundings since they often play online games.